Treatment Modality of Idiopathic Granulomatous Mastitis with Surgery Alone or in Combination with Steroid (Bioresearch Communications, 2021)
Background: Idiopathic Granulomatous Mastitis (IGM) is a rare chronic inflammatory disease. Diagnosis and treatment is still a challenge because of obscure etiology and rareness. Owing to wide spectrum of IGM it is difficult to standardize and optimize the treatment. The aim of our study was to evaluate the outcome of surgical excision or in combination with steroid in treating IGM.Methodology: A randomized controlled clinical trial was done in BIRDEM (Bangladesh Institute of Research and Rehabilitation of Diabetic, Endocrine and Metabolic Disorder) Hospital, Dhaka, Bangladesh from July’2008 to June’2018. Overall 82 patients met the inclusion criteria. We analyzed therapeutic modalities and compared the patients’ outcomes based on treatment.Results: All patients underwent wide excision with clear margin under general anesthesia. Post operatively steroid was given in 41 patients. Duration of steroid therapy was 6 months after surgery. We have seen that recovery time was short in steroid group (Gr-II) average 167.07 days in compared without steroid (Gr l) average 253.28 days. Patients who underwent surgery only (GR-I) about 49.90% patients experienced recurrence (e.g. fistula formation and inflammatory mass etc.) On the other hand, 12.1% patients developed recurrences that were treated with steroid following surgery (Gr-II).Conclusion: Surgery with steroid is more effective in treatment of idiopathic granulomatous mastitis than surgery alone.Bioresearch Commu. 7(1): 924-926, 2021 (January)